Marine decapod Crustacea of southern Australia : a guide to identification - Poore, Gary C. B. (CSIRO Pub., 2004)
This book is a comprehensive guide to the identification of 800 species of decapod and stomatopod crustaceans from southern Australian marine waters. It is liberally illustrated with more than 1000 line drawings giving good views of many species as well as diagnostic illustrations.